PRONOMINA PERSONA SAPAAN ANTARA SUAMI DAN ISTRI DALAM DIALEK MUSI: ANALISIS BENTUK DAN MAKNA - Hadi, Imron (Balai Bahasa Sumatra Barat, 2015)
This article is to describe personal pronouns of greeting di Musi dialect between husband and wife interaction. This study used descriptive qualitative method. The data were taken throughparticipant observation, recording,dan field note to some informans from three villages. The result was found that there were two phases of using greeting, pre-marriage and marriage phase. In both pre-marriage and marriage phase, there were also two forms, indirect and direct communication. In pre-marriage phase the phrasal pronouns for indirect communication were Anak wak +proper name, Anak mang/bibi+proper name. and for direct was kamu or kau.For marriage phase the phrasal pronouns for indirect communication were anak kamu, cucong kamu, anak